Durkheim y Weber: surgimiento de la Sociología jurídica y teorización del Derecho como instrumento de control social - Noguera Fernández, Albert (2006)
The purpose of this essay is to reflect on the creation of juridical sociology as an autonomous and independent science, and to review the texts of the two great founders of this discipline, Emile Durkheim and Weber. Based on their texts we shall try to establish the actual contribution of both thinkers to the birth of the juridical-sociological analysis, and to the development of a sociological approach to Law, according to which, Law cannot be only understood as a simple process of production and application of restrictive rules, but also as a process that creates new customs and social relations that build a structure of thought in citizens, and therefore becomes one of the most important mechanisms of political domination and rule, Law as an instrument of social control. .